Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s13555-021-00626-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Self-Reported Psoriasis Treatment Convenience Scale (PTCS)

Abstract: Introduction: Adherence to topical treatments for psoriasis is reported to be poor. One key contributing factor is the inconvenience associated with formulations that may be greasy, time consuming to apply, and slow to absorb. There is a paucity of patient-reported outcome measures that evaluate psoriasis patients' perceptions of treatment convenience. The Psoriasis Treatment Convenience Scale (PTCS) was therefore developed and validated. Methods: Following a literature review of issues relating to convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The PTCS is a novel and validated patient-reported outcome scale consisting of six disease-specific, self-reported questions rated on a 1–10 scale, and has been shown to be a reliable, sensitive and valid scale to evaluate the preference of topical treatment for psoriasis. 19 The mean PTCS at week 8 for CAL/BDP PAD-cream was statistically significantly higher than CAL/BDP gel/TS (40.4 versus 37.0; p <0.0001). Individual results of the PTCS questions revealed that the greater preference for CAL/BDP PAD-cream was mainly due to the gel/TS being a greasier formulation.…”
Section: Discussionmentioning
confidence: 83%
“…The PTCS is a novel and validated patient-reported outcome scale consisting of six disease-specific, self-reported questions rated on a 1–10 scale, and has been shown to be a reliable, sensitive and valid scale to evaluate the preference of topical treatment for psoriasis. 19 The mean PTCS at week 8 for CAL/BDP PAD-cream was statistically significantly higher than CAL/BDP gel/TS (40.4 versus 37.0; p <0.0001). Individual results of the PTCS questions revealed that the greater preference for CAL/BDP PAD-cream was mainly due to the gel/TS being a greasier formulation.…”
Section: Discussionmentioning
confidence: 83%
“…Convenience and aesthetic acceptability are particularly relevant to topical application, as greasiness, altered appearance and disrupted daily routines will negatively impact adherence to therapy and consequently real‐world efficacy 29 . Therefore, convenience of the treatment modality is an important factor in optimising adherence to therapy 22 . A recent survey showed that participants' most preferred vehicle was a water‐based cream and that the formulation attributes rated most important were application feel, non‐staining, quick absorption and non‐sticky texture 30 .…”
Section: Discussionmentioning
confidence: 99%
“…29 Therefore, convenience of the treatment modality is an important factor in optimising adherence to therapy. 22 A recent survey showed that participants' most preferred vehicle was a water-based cream and that the formulation attributes rated most important were application feel, non-staining, quick absorption and non-sticky texture. 30 The greater convenience scores of the PAD-cream formulation compared to gel was mainly driven by questions concerning greasiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, there is a need for validated tools to evaluate patients’ acceptance of topical therapy vehicles [ 41 ]. A psoriasis treatment convenience scale (PTCS) has been validated, consisting of five questions addressing ease of application, greasiness, moisturization and impact on the daily routine plus an overarching question regarding the patient’s overall satisfaction with the treatment [ 42 ]. Other examples of similar questionnaires are the Vehicle Preference Measure [ 43 ], the Topical Therapy Adherence Questionnaire (TTAQ) [ 44 ] and the Topical Product Usability Questionnaire (TPUQ) [ 45 ].…”
Section: Aesthetic Elegance and Satisfaction With Treatmentmentioning
confidence: 99%